SPACE NETWORK EMULATION USING HIGH-RATE DELAY TOLERANT NETWORKING - Tokbergen, Abylay (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This capstone project is intended to provide an insight into the development of a space technology, NASA’s High Rate Delay Tolerant Networking (HDTN) system, which is a breakthrough technology to compensate high rate delay tolerant networking in interplanetary networks. The work consists of designing and implementing a virtual testbed environment based on STK, Netropy, Docker Swarm and HDTN software modules. It also evaluates the performance of the DTN protocols such as BPv6, BPv7, and BPSec over LTP and TCPCL convergence layers. Realistic scenarios were tested under variable link conditions, core functions of HDTN, such as ingress, egress, routing and storage. Simulation results proved the reliability of data transmission, effective- ness of custody transfer and robustness of the encryption. Results in this thesis demonstrate that HDTN provides the potential for order of magnitude scalability, reliability and security improvement in space networks and serve as basis for future cognitive networking applications in space communication systems.
Keywords: Space; Communication; HDTN; type of access: open access